Sequence Organization of Tom Hanks and Indro Warkop in Comedy Podcast Conversations - Siti Zahra; Ice Sariyati; Erfan Muhamad Fauzi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
This research explored how sequence organization is used to build humor in podcasts, specifically in the episodes of Conan O’Brien Needs a Friend with Tom Hanks and Raditya Dika’s podcast with Indro Warkop. Using a descriptive qualitative method based on Conversation Analysis, the research utilized Schegloff's (2007) sequence organization framework as the main tool for analysis, while Norrick's (1993) conversational joking theory, Hay's (2001) humor response model, and Berger's (1993) linguistic techniques of humor were used as additional reference frameworks. Through analysis, nine instances of humor sequences were uncovered in Tom Hanks’ talk and four in that of Indro Warkop. The research disclosed that humor in both podcasts was majorly structurally dependent on non-minimal post-expansion, yet their implementation of it was quite different. Whereas Tom Hanks' jokes were mainly derived from a variety of adjacency pair types and sequences initiated by himself with quite compact punchline delivery and operated mostly through irony, exaggeration, allusion, and infantilism. Indro's humor was mostly supported on question-answer pairs as structural points of entry and narratives in post-expansion that were gradually developing comic tension before punchline delivery through exaggeration, irony, and facetiousness. The study has brought to light that sequence organization was one of the major ways through which humor was engaged with in podcast talk collaboratively.